From stdpp Require Import coPset. From iris.bi Require Import interface derived_laws_sbi big_op plainly. Import interface.bi derived_laws_bi.bi derived_laws_sbi.bi. (* We first define operational type classes for the notations, and then later bundle these operational type classes with the laws. *) Class BUpd (PROP : Type) : Type := bupd : PROP → PROP. Instance : Params (@bupd) 2. Hint Mode BUpd ! : typeclass_instances. Notation "|==> Q" := (bupd Q) : bi_scope. Notation "P ==∗ Q" := (P ⊢ |==> Q) (only parsing) : stdpp_scope. Notation "P ==∗ Q" := (P -∗ |==> Q)%I : bi_scope. Class FUpd (PROP : Type) : Type := fupd : coPset → coPset → PROP → PROP. Instance: Params (@fupd) 4. Hint Mode FUpd ! : typeclass_instances. Notation "|={ E1 , E2 }=> Q" := (fupd E1 E2 Q) : bi_scope. Notation "P ={ E1 , E2 }=∗ Q" := (P -∗ |={E1,E2}=> Q)%I : bi_scope. Notation "P ={ E1 , E2 }=∗ Q" := (P -∗ |={E1,E2}=> Q) : stdpp_scope. Notation "|={ E }=> Q" := (fupd E E Q) : bi_scope. Notation "P ={ E }=∗ Q" := (P -∗ |={E}=> Q)%I : bi_scope. Notation "P ={ E }=∗ Q" := (P -∗ |={E}=> Q) : stdpp_scope. (** Fancy updates that take a step. *) Notation "|={ E1 , E2 , E3 }▷=> Q" := (|={E1,E2}=> (▷ |={E2,E3}=> Q))%I : bi_scope. Notation "P ={ E1 , E2 , E3 }▷=∗ Q" := (P -∗ |={ E1,E2,E3 }▷=> Q)%I : bi_scope. Notation "|={ E1 , E2 }▷=> Q" := (|={E1,E2,E1}▷=> Q)%I : bi_scope. Notation "P ={ E1 , E2 }▷=∗ Q" := (P ⊢ |={ E1 , E2, E1 }▷=> Q) (only parsing) : stdpp_scope. Notation "P ={ E1 , E2 }▷=∗ Q" := (P -∗ |={ E1 , E2, E1 }▷=> Q)%I : bi_scope. Notation "|={ E }▷=> Q" := (|={E,E}▷=> Q)%I : bi_scope. Notation "P ={ E }▷=∗ Q" := (P ={E,E}▷=∗ Q)%I : bi_scope. Notation "|={ E1 , E2 }▷=>^ n Q" := (Nat.iter n (λ P, |={E1,E2}▷=> P) Q)%I : bi_scope. Notation "P ={ E1 , E2 }▷=∗^ n Q" := (P ⊢ |={E1,E2}▷=>^n Q)%I (only parsing) : stdpp_scope. Notation "P ={ E1 , E2 }▷=∗^ n Q" := (P -∗ |={E1,E2}▷=>^n Q)%I : bi_scope. (** Bundled versions *) (* Mixins allow us to create instances easily without having to use Program *) Record BiBUpdMixin (PROP : bi) `(BUpd PROP) := { bi_bupd_mixin_bupd_ne : NonExpansive bupd; bi_bupd_mixin_bupd_intro (P : PROP) : P ==∗ P; bi_bupd_mixin_bupd_mono (P Q : PROP) : (P ⊢ Q) → (|==> P) ==∗ Q; bi_bupd_mixin_bupd_trans (P : PROP) : (|==> |==> P) ==∗ P; bi_bupd_mixin_bupd_frame_r (P R : PROP) : (|==> P) ∗ R ==∗ P ∗ R; }. Record BiFUpdMixin (PROP : sbi) `(FUpd PROP) := { bi_fupd_mixin_fupd_ne E1 E2 : NonExpansive (fupd E1 E2); bi_fupd_mixin_fupd_intro_mask E1 E2 (P : PROP) : E2 ⊆ E1 → P ⊢ |={E1,E2}=> |={E2,E1}=> P; bi_fupd_mixin_except_0_fupd E1 E2 (P : PROP) : ◇ (|={E1,E2}=> P) ={E1,E2}=∗ P; bi_fupd_mixin_fupd_mono E1 E2 (P Q : PROP) : (P ⊢ Q) → (|={E1,E2}=> P) ⊢ |={E1,E2}=> Q; bi_fupd_mixin_fupd_trans E1 E2 E3 (P : PROP) : (|={E1,E2}=> |={E2,E3}=> P) ⊢ |={E1,E3}=> P; bi_fupd_mixin_fupd_mask_frame_r' E1 E2 Ef (P : PROP) : E1 ## Ef → (|={E1,E2}=> ⌜E2 ## Ef⌝ → P) ={E1 ∪ Ef,E2 ∪ Ef}=∗ P; bi_fupd_mixin_fupd_frame_r E1 E2 (P Q : PROP) : (|={E1,E2}=> P) ∗ Q ={E1,E2}=∗ P ∗ Q; }. Class BiBUpd (PROP : bi) := { bi_bupd_bupd :> BUpd PROP; bi_bupd_mixin : BiBUpdMixin PROP bi_bupd_bupd; }. Hint Mode BiBUpd ! : typeclass_instances. Arguments bi_bupd_bupd : simpl never. Class BiFUpd (PROP : sbi) := { bi_fupd_fupd :> FUpd PROP; bi_fupd_mixin : BiFUpdMixin PROP bi_fupd_fupd; }. Hint Mode BiFUpd ! : typeclass_instances. Arguments bi_fupd_fupd : simpl never. Class BiBUpdFUpd (PROP : sbi) `{BiBUpd PROP, BiFUpd PROP} := bupd_fupd E (P : PROP) : (|==> P) ={E}=∗ P. Hint Mode BiBUpdFUpd ! - - : typeclass_instances. Class BiBUpdPlainly (PROP : sbi) `{!BiBUpd PROP, !BiPlainly PROP} := bupd_plainly (P : PROP) : (|==> ■ P) -∗ P. Hint Mode BiBUpdPlainly ! - - : typeclass_instances. Class BiFUpdPlainly (PROP : sbi) `{!BiFUpd PROP, !BiPlainly PROP} := { fupd_plainly_weak E (P Q : PROP) : (Q ={E}=∗ ■ P) -∗ Q ={E}=∗ Q ∗ P; later_fupd_plainly p E1 E2 (P : PROP) : (▷?p |={E1, E2}=> ■ P) ={E1}=∗ ▷?p ◇ P; }. Hint Mode BiBUpdFUpd ! - - : typeclass_instances. Section bupd_laws. Context `{BiBUpd PROP}. Implicit Types P : PROP. Global Instance bupd_ne : NonExpansive (@bupd PROP _). Proof. eapply bi_bupd_mixin_bupd_ne, bi_bupd_mixin. Qed. Lemma bupd_intro P : P ==∗ P. Proof. eapply bi_bupd_mixin_bupd_intro, bi_bupd_mixin. Qed. Lemma bupd_mono (P Q : PROP) : (P ⊢ Q) → (|==> P) ==∗ Q. Proof. eapply bi_bupd_mixin_bupd_mono, bi_bupd_mixin. Qed. Lemma bupd_trans (P : PROP) : (|==> |==> P) ==∗ P. Proof. eapply bi_bupd_mixin_bupd_trans, bi_bupd_mixin. Qed. Lemma bupd_frame_r (P R : PROP) : (|==> P) ∗ R ==∗ P ∗ R. Proof. eapply bi_bupd_mixin_bupd_frame_r, bi_bupd_mixin. Qed. End bupd_laws. Section fupd_laws. Context `{BiFUpd PROP}. Implicit Types P : PROP. Global Instance fupd_ne E1 E2 : NonExpansive (@fupd PROP _ E1 E2). Proof. eapply bi_fupd_mixin_fupd_ne, bi_fupd_mixin. Qed. Lemma fupd_intro_mask E1 E2 (P : PROP) : E2 ⊆ E1 → P ⊢ |={E1,E2}=> |={E2,E1}=> P. Proof. eapply bi_fupd_mixin_fupd_intro_mask, bi_fupd_mixin. Qed. Lemma except_0_fupd E1 E2 (P : PROP) : ◇ (|={E1,E2}=> P) ={E1,E2}=∗ P. Proof. eapply bi_fupd_mixin_except_0_fupd, bi_fupd_mixin. Qed. Lemma fupd_mono E1 E2 (P Q : PROP) : (P ⊢ Q) → (|={E1,E2}=> P) ⊢ |={E1,E2}=> Q. Proof. eapply bi_fupd_mixin_fupd_mono, bi_fupd_mixin. Qed. Lemma fupd_trans E1 E2 E3 (P : PROP) : (|={E1,E2}=> |={E2,E3}=> P) ⊢ |={E1,E3}=> P. Proof. eapply bi_fupd_mixin_fupd_trans, bi_fupd_mixin. Qed. Lemma fupd_mask_frame_r' E1 E2 Ef (P : PROP) : E1 ## Ef → (|={E1,E2}=> ⌜E2 ## Ef⌝ → P) ={E1 ∪ Ef,E2 ∪ Ef}=∗ P. Proof. eapply bi_fupd_mixin_fupd_mask_frame_r', bi_fupd_mixin. Qed. Lemma fupd_frame_r E1 E2 (P Q : PROP) : (|={E1,E2}=> P) ∗ Q ={E1,E2}=∗ P ∗ Q. Proof. eapply bi_fupd_mixin_fupd_frame_r, bi_fupd_mixin. Qed. End fupd_laws. Section bupd_derived. Context `{BiBUpd PROP}. Implicit Types P Q R : PROP. (* FIXME: Removing the `PROP:=` diverges. *) Global Instance bupd_proper : Proper ((≡) ==> (≡)) (bupd (PROP:=PROP)) := ne_proper _. (** BUpd derived rules *) Global Instance bupd_mono' : Proper ((⊢) ==> (⊢)) (bupd (PROP:=PROP)). Proof. intros P Q; apply bupd_mono. Qed. Global Instance bupd_flip_mono' : Proper (flip (⊢) ==> flip (⊢)) (bupd (PROP:=PROP)). Proof. intros P Q; apply bupd_mono. Qed. Lemma bupd_frame_l R Q : (R ∗ |==> Q) ==∗ R ∗ Q. Proof. rewrite !(comm _ R); apply bupd_frame_r. Qed. Lemma bupd_wand_l P Q : (P -∗ Q) ∗ (|==> P) ==∗ Q. Proof. by rewrite bupd_frame_l wand_elim_l. Qed. Lemma bupd_wand_r P Q : (|==> P) ∗ (P -∗ Q) ==∗ Q. Proof. by rewrite bupd_frame_r wand_elim_r. Qed. Lemma bupd_sep P Q : (|==> P) ∗ (|==> Q) ==∗ P ∗ Q. Proof. by rewrite bupd_frame_r bupd_frame_l bupd_trans. Qed. End bupd_derived. Section bupd_derived_sbi. Context {PROP : sbi} `{BiBUpd PROP}. Implicit Types P Q R : PROP. Lemma except_0_bupd P : ◇ (|==> P) ⊢ (|==> ◇ P). Proof. rewrite /sbi_except_0. apply or_elim; eauto using bupd_mono, or_intro_r. by rewrite -bupd_intro -or_intro_l. Qed. Section bupd_plainly. Context `{BiBUpdPlainly PROP}. Lemma bupd_plain P `{!Plain P} : (|==> P) ⊢ P. Proof. by rewrite {1}(plain P) bupd_plainly. Qed. Lemma bupd_forall {A} (Φ : A → PROP) `{∀ x, Plain (Φ x)} : (|==> ∀ x, Φ x) ⊣⊢ (∀ x, |==> Φ x). Proof. apply (anti_symm _). - apply forall_intro=> x. by rewrite (forall_elim x). - rewrite -bupd_intro. apply forall_intro=> x. by rewrite (forall_elim x) bupd_plain. Qed. End bupd_plainly. End bupd_derived_sbi. Section fupd_derived. Context `{BiFUpd PROP}. Implicit Types P Q R : PROP. Global Instance fupd_proper E1 E2 : Proper ((≡) ==> (≡)) (fupd (PROP:=PROP) E1 E2) := ne_proper _. (** FUpd derived rules *) Global Instance fupd_mono' E1 E2 : Proper ((⊢) ==> (⊢)) (fupd (PROP:=PROP) E1 E2). Proof. intros P Q; apply fupd_mono. Qed. Global Instance fupd_flip_mono' E1 E2 : Proper (flip (⊢) ==> flip (⊢)) (fupd (PROP:=PROP) E1 E2). Proof. intros P Q; apply fupd_mono. Qed. Lemma fupd_intro E P : P ={E}=∗ P. Proof. by rewrite {1}(fupd_intro_mask E E P) // fupd_trans. Qed. Lemma fupd_intro_mask' E1 E2 : E2 ⊆ E1 → (|={E1,E2}=> |={E2,E1}=> bi_emp (PROP:=PROP))%I. Proof. exact: fupd_intro_mask. Qed. Lemma fupd_except_0 E1 E2 P : (|={E1,E2}=> ◇ P) ={E1,E2}=∗ P. Proof. by rewrite {1}(fupd_intro E2 P) except_0_fupd fupd_trans. Qed. Lemma fupd_frame_l E1 E2 P Q : (P ∗ |={E1,E2}=> Q) ={E1,E2}=∗ P ∗ Q. Proof. rewrite !(comm _ P); apply fupd_frame_r. Qed. Lemma fupd_wand_l E1 E2 P Q : (P -∗ Q) ∗ (|={E1,E2}=> P) ={E1,E2}=∗ Q. Proof. by rewrite fupd_frame_l wand_elim_l. Qed. Lemma fupd_wand_r E1 E2 P Q : (|={E1,E2}=> P) ∗ (P -∗ Q) ={E1,E2}=∗ Q. Proof. by rewrite fupd_frame_r wand_elim_r. Qed. Lemma fupd_mask_weaken E1 E2 P `{!Absorbing P} : E2 ⊆ E1 → P ={E1,E2}=∗ P. Proof. intros ?. rewrite -{1}(right_id emp%I bi_sep P%I). rewrite (fupd_intro_mask E1 E2 emp%I) //. by rewrite fupd_frame_l sep_elim_l. Qed. Lemma fupd_trans_frame E1 E2 E3 P Q : ((Q ={E2,E3}=∗ emp) ∗ |={E1,E2}=> (Q ∗ P)) ={E1,E3}=∗ P. Proof. rewrite fupd_frame_l assoc -(comm _ Q) wand_elim_r. by rewrite fupd_frame_r left_id fupd_trans. Qed. Lemma fupd_elim E1 E2 E3 P Q : (Q -∗ (|={E2,E3}=> P)) → (|={E1,E2}=> Q) -∗ (|={E1,E3}=> P). Proof. intros ->. rewrite fupd_trans //. Qed. Lemma fupd_mask_frame_r E1 E2 Ef P : E1 ## Ef → (|={E1,E2}=> P) ={E1 ∪ Ef,E2 ∪ Ef}=∗ P. Proof. intros ?. rewrite -fupd_mask_frame_r' //. f_equiv. apply impl_intro_l, and_elim_r. Qed. Lemma fupd_mask_mono E1 E2 P : E1 ⊆ E2 → (|={E1}=> P) ={E2}=∗ P. Proof. intros (Ef&->&?)%subseteq_disjoint_union_L. by apply fupd_mask_frame_r. Qed. (** How to apply an arbitrary mask-changing view shift when having an arbitrary mask. *) Lemma fupd_mask_frame E E' E1 E2 P : E1 ⊆ E → (|={E1,E2}=> |={E2 ∪ (E ∖ E1),E'}=> P) -∗ (|={E,E'}=> P). Proof. intros ?. rewrite (fupd_mask_frame_r _ _ (E ∖ E1)); last set_solver. rewrite fupd_trans. assert (E = E1 ∪ E ∖ E1) as <-; last done. apply union_difference_L. done. Qed. (* A variant of [fupd_mask_frame] that works well for accessors: Tailored to elliminate updates of the form [|={E1,E1∖E2}=> Q] and provides a way to transform the closing view shift instead of letting you prove the same side-conditions twice. *) Lemma fupd_mask_frame_acc E E' E1(*Eo*) E2(*Em*) P Q : E1 ⊆ E → (|={E1,E1∖E2}=> Q) -∗ (Q -∗ |={E∖E2,E'}=> (∀ R, (|={E1∖E2,E1}=> R) -∗ |={E∖E2,E}=> R) -∗ P) -∗ (|={E,E'}=> P). Proof. intros HE. apply wand_intro_r. rewrite fupd_frame_r. rewrite wand_elim_r. clear Q. rewrite -(fupd_mask_frame E E'); first apply fupd_mono; last done. (* The most horrible way to apply fupd_intro_mask *) rewrite -[X in (X -∗ _)](right_id emp%I). rewrite (fupd_intro_mask (E1 ∖ E2 ∪ E ∖ E1) (E ∖ E2) emp%I); last first. { rewrite {1}(union_difference_L _ _ HE). set_solver. } rewrite fupd_frame_l fupd_frame_r. apply fupd_elim. apply fupd_mono. eapply wand_apply; last (apply sep_mono; first reflexivity); first reflexivity. apply forall_intro=>R. apply wand_intro_r. rewrite fupd_frame_r. apply fupd_elim. rewrite left_id. rewrite (fupd_mask_frame_r _ _ (E ∖ E1)); last set_solver+. rewrite {4}(union_difference_L _ _ HE). done. Qed. Lemma fupd_mask_same E E1 P : E = E1 → (|={E}=> P) -∗ (|={E,E1}=> P). Proof. intros <-. done. Qed. Lemma fupd_sep E P Q : (|={E}=> P) ∗ (|={E}=> Q) ={E}=∗ P ∗ Q. Proof. by rewrite fupd_frame_r fupd_frame_l fupd_trans. Qed. Lemma fupd_big_sepL {A} E (Φ : nat → A → PROP) (l : list A) : ([∗ list] k↦x ∈ l, |={E}=> Φ k x) ={E}=∗ [∗ list] k↦x ∈ l, Φ k x. Proof. apply (big_opL_forall (λ P Q, P ={E}=∗ Q)); auto using fupd_intro. intros P1 P2 HP Q1 Q2 HQ. by rewrite HP HQ -fupd_sep. Qed. Lemma fupd_big_sepM `{Countable K} {A} E (Φ : K → A → PROP) (m : gmap K A) : ([∗ map] k↦x ∈ m, |={E}=> Φ k x) ={E}=∗ [∗ map] k↦x ∈ m, Φ k x. Proof. apply (big_opM_forall (λ P Q, P ={E}=∗ Q)); auto using fupd_intro. intros P1 P2 HP Q1 Q2 HQ. by rewrite HP HQ -fupd_sep. Qed. Lemma fupd_big_sepS `{Countable A} E (Φ : A → PROP) X : ([∗ set] x ∈ X, |={E}=> Φ x) ={E}=∗ [∗ set] x ∈ X, Φ x. Proof. apply (big_opS_forall (λ P Q, P ={E}=∗ Q)); auto using fupd_intro. intros P1 P2 HP Q1 Q2 HQ. by rewrite HP HQ -fupd_sep. Qed. (** Fancy updates that take a step derived rules. *) Lemma step_fupd_wand E1 E2 E3 P Q : (|={E1,E2,E3}▷=> P) -∗ (P -∗ Q) -∗ |={E1,E2,E3}▷=> Q. Proof. apply wand_intro_l. by rewrite (later_intro (P -∗ Q)%I) fupd_frame_l -later_sep fupd_frame_l wand_elim_l. Qed. Lemma step_fupd_mask_frame_r E1 E2 E3 Ef P : E1 ## Ef → E2 ## Ef → (|={E1,E2,E3}▷=> P) ⊢ |={E1 ∪ Ef,E2 ∪ Ef,E3 ∪ Ef}▷=> P. Proof. intros. rewrite -fupd_mask_frame_r //. do 2 f_equiv. by apply fupd_mask_frame_r. Qed. Lemma step_fupd_mask_mono E1 E2 F1 F2 P : F1 ⊆ F2 → E1 ⊆ E2 → (|={E1,F2}▷=> P) ⊢ |={E2,F1}▷=> P. Proof. intros ??. rewrite -(emp_sep (|={E1,F2}▷=> P)%I). rewrite (fupd_intro_mask E2 E1 emp%I) //. rewrite fupd_frame_r -(fupd_trans E2 E1 F1). f_equiv. rewrite fupd_frame_l -(fupd_trans E1 F2 F1). f_equiv. rewrite (fupd_intro_mask F2 F1 (|={_,_}=> emp)%I) //. rewrite fupd_frame_r. f_equiv. rewrite [X in (X ∗ _)%I]later_intro -later_sep. f_equiv. rewrite fupd_frame_r -(fupd_trans F1 F2 E2). f_equiv. rewrite fupd_frame_l -(fupd_trans F2 E1 E2). f_equiv. by rewrite fupd_frame_r left_id. Qed. Lemma step_fupd_intro E1 E2 P : E2 ⊆ E1 → ▷ P -∗ |={E1,E2}▷=> P. Proof. intros. by rewrite -(step_fupd_mask_mono E2 _ _ E2) // -!fupd_intro. Qed. Lemma step_fupd_frame_l E1 E2 R Q : (R ∗ |={E1, E2}▷=> Q) -∗ |={E1, E2}▷=> (R ∗ Q). Proof. rewrite fupd_frame_l. apply fupd_mono. rewrite [P in P ∗ _ ⊢ _](later_intro R) -later_sep fupd_frame_l. by apply later_mono, fupd_mono. Qed. Lemma step_fupd_fupd E P: (|={E, ∅}▷=> P) ⊣⊢ (|={E, ∅}▷=> |={E}=> P). Proof. apply (anti_symm (⊢)). - by rewrite -fupd_intro. - by rewrite fupd_trans. Qed. Lemma step_fupdN_mono E1 E2 n P Q : (P ⊢ Q) → (|={E1, E2}▷=>^n P) ⊢ (|={E1, E2}▷=>^n Q). Proof. intros HPQ. induction n as [|n IH]=> //=. rewrite IH //. Qed. Lemma step_fupdN_S_fupd n E P: (|={E, ∅}▷=>^(S n) P) ⊣⊢ (|={E, ∅}▷=>^(S n) |={E}=> P). Proof. apply (anti_symm (⊢)); rewrite !Nat_iter_S_r; apply step_fupdN_mono; rewrite -step_fupd_fupd //. Qed. Lemma step_fupdN_frame_l E1 E2 n R Q : (R ∗ |={E1, E2}▷=>^n Q) -∗ |={E1, E2}▷=>^n (R ∗ Q). Proof. induction n as [|n IH]; simpl; [done|]. rewrite step_fupd_frame_l IH //=. Qed. Section fupd_plainly_derived. Context `{BiPlainly PROP, !BiFUpdPlainly PROP}. Lemma fupd_plain_weak E P Q `{!Plain P}: (Q ={E}=∗ P) -∗ Q ={E}=∗ Q ∗ P. Proof. by rewrite {1}(plain P) fupd_plainly_weak. Qed. Lemma later_fupd_plain p E1 E2 P `{!Plain P} : (▷?p |={E1, E2}=> P) ={E1}=∗ ▷?p ◇ P. Proof. by rewrite {1}(plain P) later_fupd_plainly. Qed. Lemma fupd_plain_strong E1 E2 P `{!Plain P} : (|={E1, E2}=> P) ={E1}=∗ ◇ P. Proof. by apply (later_fupd_plain false). Qed. Lemma fupd_plain' E1 E2 E2' P Q `{!Plain P} : E1 ⊆ E2 → (Q ={E1, E2'}=∗ P) -∗ (|={E1, E2}=> Q) ={E1}=∗ (|={E1, E2}=> Q) ∗ P. Proof. intros (E3&->&HE)%subseteq_disjoint_union_L. apply wand_intro_l. rewrite fupd_frame_r. rewrite fupd_plain_strong fupd_except_0 fupd_plain_weak wand_elim_r. rewrite (fupd_mask_mono E1 (E1 ∪ E3)); last by set_solver+. rewrite fupd_trans -(fupd_trans E1 (E1 ∪ E3) E1). apply fupd_mono. rewrite -fupd_frame_r. apply sep_mono; auto. apply fupd_intro_mask; set_solver+. Qed. Lemma fupd_plain E1 E2 P Q `{!Plain P} : E1 ⊆ E2 → (Q -∗ P) -∗ (|={E1, E2}=> Q) ={E1}=∗ (|={E1, E2}=> Q) ∗ P. Proof. intros HE. rewrite -(fupd_plain' _ _ E1) //. apply wand_intro_l. by rewrite wand_elim_r -fupd_intro. Qed. Lemma step_fupd_plain E P `{!Plain P} : (|={E, ∅}▷=> P) ={E}=∗ ▷ ◇ P. Proof. specialize (later_fupd_plain true ∅ E P) => //= ->. rewrite fupd_trans fupd_plain_strong. apply fupd_mono, except_0_later. Qed. Lemma step_fupdN_plain E n P `{!Plain P}: (|={E, ∅}▷=>^n P) ={E}=∗ ▷^n ◇ P. Proof. induction n as [|n IH]. - rewrite -fupd_intro. apply except_0_intro. - rewrite Nat_iter_S step_fupd_fupd IH ?fupd_trans step_fupd_plain. apply fupd_mono. destruct n; simpl. * by rewrite except_0_idemp. * by rewrite except_0_later. Qed. End fupd_plainly_derived. End fupd_derived.